2010
DOI: 10.1038/jid.2010.100
|View full text |Cite
|
Sign up to set email alerts
|

NF-1Score: A Prediction Score for Internal Neurofibromas in Neurofibromatosis-1

Abstract: NF-1 is associated with a 15-year decrease in life expectancy. Internal neurofibromas are associated with increased morbidity and mortality through malignant transformation and compression of neighboring organs. Our purpose was to develop and to validate a clinical score for predicting internal neurofibromas in adults. The development sample comprised 208 patients and the validation sample 191 patients. The score was developed using logistic regression. Discrimination and calibration of the model were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 25 publications
3
32
2
2
Order By: Relevance
“…In NF1 patients, decreasing number of cafe-au-lait macules correlated with the presence, but not volume, of internal neurofibromas (Figure 3). This finding, which was reported recently,[14] was not explained by increasing age since this variable was included in the multivariate model. An inverse relationship between the presence of neurofibromas and café-au-lait macules – the two cardinal features of NF1 – has been reported in rare variants of NF1.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In NF1 patients, decreasing number of cafe-au-lait macules correlated with the presence, but not volume, of internal neurofibromas (Figure 3). This finding, which was reported recently,[14] was not explained by increasing age since this variable was included in the multivariate model. An inverse relationship between the presence of neurofibromas and café-au-lait macules – the two cardinal features of NF1 – has been reported in rare variants of NF1.…”
Section: Discussionsupporting
confidence: 82%
“…We then used multivariable linear regression to analyze the relationship between tumor volume and clinical/demographic factors in patients with at least one internal tumor. In our analysis, we included clinical and demographic factors previously associated with paraspinal neurofibromas in NF1 and with disease severity in NF2[14][16]; we included additional clinical factors to explore their relationship with tumor burden. For multivariable analyses, we included age, gender, inheritance pattern (sporadic vs. familial), number of café-au-lait macules (0 vs. 1–5 vs. 6–15, vs. >15), and history of skeletal abnormalities as covariates in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Among the clinical characteristics, we selected those known to be associated with mortality in children with NF1 (plexiform neurofibromas) or showing trends toward an association with mortality in NF1 patients (subcutaneous neurofibromas, absence of cutaneous neurofibromas, and short stature) [21]. Special attention was also given to clinical characteristics independently associated with internal neurofibromas in adult NF1 patients, namely, fewer than 6 café-au-lait spots, age ≤30 years (a criterion met by all our patients), and subcutaneous and cutaneous neurofibromas [16]. Most of the other clinical characteristics selected for our study were easily identified by physical examination, with the exception of Lisch nodules, which were evaluated by slit lamp examination.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover internal neurofibromas grow faster in young patients [15]. In previous work, we developed a simple scoring system (the NF1Score) that accurately predicted the presence of internal neurofibromas at risk for transformation to MPNST in adults with NF1 [16]. Four characteristics were independently associated with internal neurofibromas: presence of subcutaneous neurofibromas, fewer than 6 café-au-lait spots, absence of cutaneous neurofibromas, and age ≤30 years.…”
Section: Introductionmentioning
confidence: 99%
“…After a general increase in the number of NF with age, no significant increase was seen after 50 years. The strong association between malignant peripheral nerve sheath tumors and internal NF could partly explain this phenomenon [11,12]. Indeed the presence of internal NF has recently been associated with 4 independent factors: ≥2 subcutaneous NF, age ≤30 years, no cutaneous NF, <6 CLS.…”
Section: Discussionmentioning
confidence: 99%